ANALISIS KEBERHASILAN SISTEM INFORMASI MANAJEMEN DALAM MENDUKUNG PROSES BISNIS DI DUNIA PENDIDIKAN - Madina, Novita Rolinsa; Sompito, Nursyahrain (Universitas Bina Taruna Gorontalo, 2024)
Abstract Analysis of the Success of Management Information Systems in Supporting Business Processes in the World of Education. Background: MIS functions as a tool that facilitates effective and efficient data management in an educational environment. An integrated system that combines data about students, instructors, curriculum, finances, and infrastructure can make it easier for various stakeholders to access and manage information. Educational institutions can use SIM to make decisions based on accurate and relevant data more quickly and precisely. Research objective: the aim is to analyze the success of management information systems in supporting business processes in the world of education. Research method: the research method used in this study is a quantitative research method with a survey approach. Research results: The research results show that system quality has a significant effect on business process efficiency. User satisfaction also has a significant influence on business process efficiency. The results of this research show that the implementation of SIM has a positive impact on the efficiency of business processes in the world of education. Conclusion: The results of this study indicate that the success of SIM implementation is influenced by system quality and user satisfaction. The tables and graphs displayed support the finding that MIS has significantly improved the efficiency of educational business processes